Frequency of aspirin use in patients with type 2 diabetes: Is there any effect of concomitant diseases? - Karaca, Aslı Azakoglu; Yakar, Burkay (My University, 2019)
Aim: Current guidelines recommend the use of low-dose aspirin in diabetic patients with increased cardiovascular disease risk withno risk of bleeding to prevent cardiovascular events. The aim of this study was to investigate the frequency of aspirin use in Type 2Diabetes Mellitus and the effects of concomitant diseases.Material and Methods: Our retrospective and cross-sectional study was planned of data for rate of aspirin use in Type 2 Diabetesmellitus patients. In our study, the socio - demographic characteristics of the participants, their concomitant diseases with Type2 DM and the drugs they used were questioned. Chi-square test was used for the analysis of categorical variables. P<0.05 wasconsidered statistically significant.Results: The mean age of the 910 participants was 57.27±10,00. 64.2% of the participants were female and 35.8% were male.Hypertension was the most common concomitant disease in type 2 DM. The prevalence of aspirin use was found to be %38.6. Thereis a statistically significant difference between aspirin use rates according to genders (p <0.05). Aspirin use was significantly higherin those who quit smoking and those with concomitant disease with type 2 DM. (p<0.05).Conclusion: The rate of aspirin use in our diabetic group was insufficient. In order to increase the use and awareness of aspirin, thefactors affecting the use of aspirin should be investigated.
Keywords: Tıbbi Araştırmalar Deneysel; Endokrinoloji ve Metabolizma; Genel ve Dahili Tıp; Kalp ve Kalp Damar Sistemi